Counter anion effects on the energy density of Ni(II)-chelated tetradentate azamacrocyclic complex cation as single redox couple for non-aqueous flow batteries. (10th June 2019) - Kim, Hyun-seung; Hwang, Seunghae; Mun, Junyoung; Park, Hosang; Ryu, Ji Heon; Oh, Seung M.
Abstract: Tailoring the energy density of Ni(II)-chelated complex cation is accomplished by substituting various counter anions. Larger-sized anions are favored for increasing both the solubility and working voltage. The former advantage with larger-sized anion can be readily assumed since the binding energy is smaller to allow a higher solubility in solvents. The latter comes from the fact that Ni(II)(cyclam) complex cation in square-planar geometry shows a higher working voltage. Furthermore, the solubility of redox couple is enhanced by increasing the dielectric constant of used solvent. Consequently, the largest anion (TFSI − ) demonstrates the most promising physicochemical/electrochemical properties; the energy density of redox couple reaches 27.3 W h L −1 with the working voltage, 2.55 V. The Ni(cyclam)[TFSI]2 shows very reversible electrochemistry in 1.0  M TEABF4 in EC/PC (1:1 =  v/v ) electrolyte and presents stable cycleability at non-flowing coin type static cell.